2001
DOI: 10.1007/s002530000583
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osmotic pressure on the membrane fluidity of Saccharomyces cerevisiae at different physiological temperatures

Abstract: Membrane fluidity in whole cells of Saccharomyces cerevisiae W303-1A was estimated from fluorescence polarization measurements using the membrane probe, 1,6-diphenyl-1,3,5-hexatriene, over a wide range of temperatures (6-35 degrees C) and at seven levels of osmotic pressure between 1.38 MPa and 133.1 MPa. An increase in phase transition temperatures was observed with increasing osmotic pressure. At 1.38 MPa, a phase transition temperature of 12 +/- 2 degrees C was observed, which increased to 17 +/- 4 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 28 publications
1
74
1
Order By: Relevance
“…Membrane fluidity is believed to play a crucial role in stress resistance, and the relationship between fluidity and stress resistance has been used to predict the outcome of cell resistance to stress (15,24,39). The membrane composition of yeast during stress has been extensively studied, and it was reported that more unsaturation in the membrane increased the sensitivity to heat (40).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane fluidity is believed to play a crucial role in stress resistance, and the relationship between fluidity and stress resistance has been used to predict the outcome of cell resistance to stress (15,24,39). The membrane composition of yeast during stress has been extensively studied, and it was reported that more unsaturation in the membrane increased the sensitivity to heat (40).…”
Section: Discussionmentioning
confidence: 99%
“…In development of HVA, Sinensky (Sinensky, 1974) observed using Electron Spin Resonance (ESR) that the order parameter of E. coli membranes remained constant, determined as a function of spin probe rotational correlation time, despite their phospholipid compositions changing in response to different growth temperatures. Subsequently, evidence for HVA as a conserved evolutionary mechanism emerged (Behan-Martin et al, 1993;Cossins and Prosser, 1978) and HVA has since been reported under many other changing environmental conditions, such as in response to hydrostatic pressure (Behan et al, 1992;Macdonald, 1986, 1984), osmotic pressure (Laroche et al, 2001) , low magnetic field strength (Santoro et al, 1997) and chemicals such as PCB-153 (Gonzalez et al, 2013), mitelfosine (Rybczynska et al, 2001) and crude oil (Mazzella et al, 2005). To date evidence for HVA has been found in species across the three domains of life and it is arguably the most widely used theory to explain phospholipid compositional changes, usually through the concept of maintaining membrane fluidity or membrane viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, reduced incubation temperatures increase the molecular order of membrane lipids, i.e., rigidification (29), and alter the activity of membrane-associated enzymes and transporters (5). Other stresses, e.g., heat shock, freezing, and osmotic stress, induce dramatic changes in the organization and dynamic properties of membrane lipids (12,27). To date, most of the research in this field has focused on the connections between the physical state of the membrane and cold tolerance.…”
mentioning
confidence: 99%